Interferon restores replication fork stability and cell viability in BRCA-defective cells via ISG15 - Moro, Ramona N.; Biswas, Uddipta; Kharat, Suhas S.; Duzanic, Filip D.; Das, Prosun; Stavrou, Maria; Raso, Maria C.; Freire, Raimundo; Chaudhuri, Arnab Ray; Sharan, Shyam K.; Penengo, Lorenza (Nature communications, 2023)
DNA replication and repair defects or genotoxic treatments trigger interferon (IFN)-mediated inflammatory responses. However, whether and how IFN signaling in turn impacts the DNA replication process has remained elusive. Here we show that basal levels of the IFN-stimulated gene 15, ISG15, and its conjugation (ISGylation) are essential to protect nascent DNA from degradation. Moreover, IFNβ treatment restores replication fork stability in BRCA1/2-deficient cells, which strictly depends on topoisomerase-1, and rescues lethality of BRCA2-deficient mouse embryonic stem cells. Although IFNβ activates hundreds of genes, these effects are specifically mediated by ISG15 and ISGylation, as their inactivation suppresses the impact of IFNβ on DNA replication. ISG15 depletion significantly reduces cell proliferation rates in human BRCA1-mutated triple-negative, whereas its upregulation results in increased resistance to the chemotherapeutic drug cisplatin in mouse BRCA2-deficient breast cancer cells, respectively. Accordingly, cells carrying BRCA1/2 defects consistently show increased ISG15 levels, which we propose as an in-built mechanism of drug resistance linked to BRCAness. Here the authors show that the basal activation of the interferon/ISG15 pathway is required for the stability of nascent DNA during replication and its upregulation promotes viability, proliferation and acquisition of drug resistance in BRCA1/2 deficient cells.